Detection of Vancomycin Resistance among Methicillin-Resistant Staphylococcus aureus Strains Recovered from Children with Invasive Diseases in a Reference Pediatric Hospital - Pardo, Lorena (2024)
Vancomycin is the cornerstone in treating methicillin-resistant Staphylococcus aureus (MRSA) infections. However, therapeutic failures can occur when MRSA strains with decreased susceptibility to glycopeptides (DSG) are involved. The aim of this study was to detect and characterize DSG in MRSArecovered from children with invasive diseases at a reference pediatric hospital between 2009 and2019. Fifty-two MRSAstrains werescreenedusingagarplates with vancomycin3 and 4 mg/L (BHI-3 and BHI-4); the VITEK2 system; and standard and macro E-tests. Suspicious hVISA were studied by population analysis profiling–area under the curve (PAP-AUC), and wall thickness was analyzed by transmission electron microscopy. Neither VRSA nor VISA were detected in this set. As only three strains met the hVISA criteria, the PAP-AUC study included 12 additional MRSA strains that grew one colony on BHI-4 plates or showed minimum inhibitory concentrations of vancomycin and/or teicoplanin 1.5 mg/L. One strain was confirmed as hVISA by PAP-AUC. The wall thickness was greater than the vancomycin-susceptible control strain; it belonged to ST30 and carried SCCmec IV. As expected, a low frequency of hVISA was found (1.9%). The only hVISA confirmed by PAP-AUC wasnot detected by the screening methods, highlighting the challenge that its detection represents for microbiology laboratories.